Pengaruh Kompetensi Komunikatif Guru Terhadap Antusiasme Belajar Pendidikan Pancasila Siswa Kelas IX MTs Tasymirusy Syubban Tedunan Jepara - Muhammad Aditya Rohman; Sutomo; Sri Widayati (Action Research Journal, 2025)
This research is motivated by the delivery of material from Pancasila Education teachers, which tends to be monotonous and lacks variety, as well as the less than optimal indicators of teacher communicative competence, such as being able to ask questions that encourage students to explore the learning material themselves, being able to ask questions that encourage high-level questions, and being skilled in various interaction techniques to prevent boredom. The purpose of this study is to determine the influence of teacher communicative competence on the enthusiasm of learning Pancasila Education of grade IX students of MTs Tasymirusy Syubban Tedunan Jepara. This study is a study with a quantitative research design. The population in this study was grade IX students of MTs Tasymirusy Syubban Tedunan Jepara, with a population of 56 students. While the sample in this study were all grade IX B students of MTs Tasymirusy Syubban Tedunan, totaling 30 students. The sampling technique applied was cluster random sampling. The data collection technique used a questionnaire, and data analysis used a normality test, determination test, and F test with the help of the SPSS 25 program. The results of the study stated that there was a significant influence between teacher communicative competence and the enthusiasm for learning Pancasila Education of class IX students of MTs Tasymirusy Syubban Tedunan Jepara; this was indicated by the value of the F test results of 5.869, which was greater than the F table of 4.200, or a sig value smaller than alpha 0.050 (0.022 < 0.050). Teacher communicative competence had an influence of 17.300%, indicated by a determination value of 0.173. Based on the results of the research that had been carried out, it could be concluded that each variable had a relationship.